An atlas of African affairs - Boyd, Andrew, 1920-2003.; Van Rensburg, Patrick, 1931-; Bromage, W. H. (New York, Praeger, 1962)
Africa as it was up until 1962.
Keywords: Travel; Africa -- Maps; Africa -- Description and travel; atlases; Atlases; Maps; Atlases; Maps; Atlas